Diversity of controllable anonymous communication system - Yan-wei ZHOU; Zhen-qiang WU; Bo YANG (Tongxin xuebao)
With the development of network communication technology,the Tor anonymous communication system has been widely used.However,there are also some unsafe factors such as insufficient anonymity which deserves to be noticed.Thus,a diversified controllable anonymous communication system (DC-ACS) was proposed based on the node regional management strategy.The diversified anonymous link establishment mechanism chooses nodes in the corresponding field to build the anonymous communication link according to users’ needs,controls users’ malicious anonymous activities,and ensures the anonymity of senders and receivers to the first and last node of anonymous communication link.Compared with the Tor anonymous communication system,DC-ACS not only has anonymity,but also has higher security and anti-attack capability,which eliminated potential security risks existed in the Tor anonymous communications system.